'Rinse and Replace': Boosting T Cell Turnover To Reduce HIV-1 Reservoirs. Issue 6 (June 2020) - ,; Kawabe, Takeshi; Bocharov, Gennady; Meier-Schellersheim, Martin; Alon, Hagit; Chomont, Nicolas; Grossman, Zehava; Sousa, Ana E; Margolis, Leonid; Maldarelli, Frank; Grossman, Zvi; Singh, Nevil J.; et al.
Abstract : Latent HIV-1 persists indefinitely during antiretroviral therapy (ART) as an integrated silent genome in long-lived memory CD4 + T cells. In untreated infections, immune activation increases the turnover of intrinsically long-lived provirus-containing CD4 + T cells. Those are 'washed out' as a result of their activation, which when coupled to viral protein expression can facilitate local inflammation and recruitment of uninfected cells to activation sites, causing latently infected cells to compete for survival. De novo infection can counter this washout. During ART, inflammation and CD4 + T cell activation wane, resulting in reduced cell turnover and a persistent reservoir. We propose accelerating reservoir washout during ART by triggering sequential waves of polyclonal CD4 + T cell activation while simultaneously enhancing virus protein expression. Reservoir reduction as an adjunct to other therapies might achieve lifelong viral control. Highlights: A substantial reduction of the HIV-1 reservoir is not a cure but can have a profound effect by acting synergistically with additional modalities, together reducing the probability of spontaneous viral breakout in the absence of ART in a multiplicative (rather than additive) manner. The currently pursued strategy is 'shock and kill', which aims to reactivate the latent virus extensively during ART, thus subjecting host cells to killing via activated virus or cytotoxic T cells. This has proven to be most challenging. The proposed alternative is 'rinse and replace': inducing waves of polyclonal T cell activation during ART, while enhancing HIV-1 viral protein expression, to boost the differentiation and subsequent death of infected CD4 + T cells and their replacement by uninfected cells. Nature itself has provided a proof of principle: although chronic activation is a leading cause of AIDS, in the short run it limits the number of infected cells and the diversity of replicating virus. The turnover of cells containing HIV-1 DNA is accelerated during untreated infection. This acceleration is imposed by the concomitant regulation of immune activation and homeostasis. The well-documented phenomenology and theory of 'proximal immune activation and HIV transmission' applies to microdynamic events underlying accelerated turnover: localized, dendritic cell-centered bursts of T cell activation and HIV-1 transmission, sparked/enhanced by latently infected cells, recruitment of bystander cells, self-limiting accumulation of memory cells, and 'wax and wane' kinetics of T cell clones and HIV-1 variants. 'Rinse and replace' aims to mimic these events under ART – to generate a flux of memory CD4 + T cells capable of carrying away the infected cells with minimal side effects.